v.2 - "Wicksteed, Philip H." (London, 1957)
The first volume contains one of the best general introductions to economics written. It gives an ex position of the marginal analysis; of the notions of margins and limiting rates of expenditure; of the phenomena of money and exchange; of the implications of the economic nexus; of markets,, earnings, and interest; and finally of the inter-relations of distribu tion and production - costs with reference to economic equilibri um. The system thus explained is then applied to such practical problems as housing, unemploy ment, redistribution of wealth. taxation, land nationalization, socialism, etc. The second volume contains a series of special studies of technical problems of analysis, and is of prime importance to advanced students.
Keywords: Economics